The effects of oral health education regarding periodontal health on non-dental undergraduates in southwestern China-exploring the feasibility of an e-learning course for oral health promotion - Zhiwu Wu; Mingming Li; Fangzhi Zhu; Lei Lei; Ran Cheng; Tao Hu (BMC, 2021)
Abstract Background The high prevalence of periodontal diseases is an important oral health problem worldwide. It is necessary to increase public knowledge on and influence attitudes towards periodontal diseases in order to prevent them. However, the effect of oral health education (OHE) as a primary preventive method in China is unsatisfactory. The aim of this study is to investigate the feasibility of extending an e-learning course regarding periodontal health by comparing the effects of oral health education regarding periodontal health (OHE-PH) on dental and non-dental students and the effects between a traditional course and an e-learning course among non-dental students at Sichuan University. Methods A quasi-experimental study with a pre-test and a post-test was performed. A total of 217 dental students and 134 non-dental students attended a traditional course; 69 non-dental students attended an e-learning course. Before- and after-course questionnaires about periodontal health knowledge, attitudes and behaviours were administered. Results After the traditional/e-learning course, the knowledge of both dental and non-dental students about periodontal diseases and self-reported behaviours for gingival bleeding and oral care improved. The non-dental students reached or surpassed the level of dental students before the course. The non-dental students taking the e-learning course performed better in some areas than those taking the traditional course. Conclusions OHE-PH was effective for dental and non-dental students. The e-learning course on OHE-PH was sufficient for improving knowledge and self-reported behaviours among non-dental undergraduates and was even better than the traditional course in some areas. The e-learning course may be an effective method for periodontal health education and oral health promotion among undergraduates.